Modeling and mechanical properties of glass fiber reinforced nylon - Muhammad Syafiq, Mohd Zamil (2016)
Nylon is one of synthetic polymers known as polyamides. Although nylon has many advantages in terms of physical properties and mechanical properties. However the advantages of plastic nylon improvements need to be made to obtain better physical properties and mechanical properties. The combination of the two types of glass-reinforced nylon 6 and nylon fibers, generate of plastic composite materials. This study aims to analyze model and the properties of glass fiber reinforced nylon. This study used CATIA V5 software for producing modeling of dog bone shaped specimens according to ASTM D638 standard size. Modeling specimen are complete with feed system. Modeling the three different locations for injection of entrance door pin, the central door, and the door edge. Autodesk Moldflow Insight software is used to identify the appropriate process flow between the three different doors for the injection molding process. Then, the injection molding machine is used to produce specimens of glass fiber reinforced nylon in shaped of dog bone with different percentages of glass fiber. The percentage of glass fiber used is 5%, 10%, 15% and 20%. The temperature used to mix two materials (nylon and fiberglass) is between 230 ° C to 258 ° C. Lastly the process of studying physical properties and mechanical by using universal tensile machine and pendulum impactor machine. Universal tensile machine is used to generate the tensile stress-strain graphs for each specimen and the tensile strength for each of the tests were analyzed by using three different rates of 3mm / min, 5mm / min and 10mm / min. Pendulum impactor is used to perform impact tests. Specimens according to ASTM D4812 and the hammer 50 J used during the impact test. In conclusion, the percentage of glass fiber mixture higher achieve higher tensile stress at maximum temperature. This is because the total weight of glass fiber nylon reinforced increased as a percentage of glass fibers increases. The difference between the tensile strength of pure nylon and glass fiber reinforced scheduled and in plot in the graph.